Pengaruh Literasi Keuangan, Kompetensi Sumber Daya Manusia Dan Minat Menggunakan E-commerce Terhadap Kinerja Keuangan UMKM Pada Masa Pandemi COVID-19 di Kecamatan Buleleng - I Gusti Ayu Dhara Kartika Sari; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2022)
The financial performance of Micro, Small, and Medium Enterprises is an attempt by every company to measure and assess a success that is used to generate profits. This study aims to determine the partial effect of financial literacy, human resource competence, and interest in using e- commerce on financial performance in the Buleleng District. The type of data used is quantitative data. Sources of data in this study, namely primary data using techniques survey (questionnaires). The population in this study are Micro, Small, and Medium Enterprises in Buleleng District. The sampling technique used is the purposive sampling technique with a total sample of 29 villages and the number of respondents as many as 49 people. Data analysis in this study used SPSS version 16 for windows. The results of this study indicate that financial literacy, human resource competence, and interest in using e-commerce have a positive and partially significant effect on financial performance in Micro, Small, and Medium Enterprises in Buleleng District. Based on the results of this study, it can be seen that the three independent variables have a positive and significant effect on financial performance.